Sensitivity of GC-EI/MS, GC-EI/MS/MS, LC-ESI/MS/MS, LC-Ag+CIS/MS/MS, and GC-ESI/MS/MS for analysis of anabolic steroids in doping control - Cha, Eunju; Kim, Sohee; Kim, Ho Jun; Lee, Kang Mi; Kim, Ki Hun; Kwon, Oh-Seung; Lee, Jaeick (WILEY-BLACKWELL, 2015)
This study compared the sensitivity of various separation and ionization methods, including gas chromatography with an electron ionization source (GC-EI), liquid chromatography with an electrospray ionization source (LC-ESI), and liquid chromatography with a silver ion coordination ion spray source (LC-Ag+CIS), coupled to a mass spectrometer (MS) for steroid analysis. Chromatographic conditions, mass spectrometric transitions, and ion source parameters were optimized. The majority of steroids in GC-EI/MS/MS and LC-Ag+CIS/MS/MS analysis showed higher sensitivities than those obtained with other analytical methods. The limits of detection (LODs) of 65 steroids by GC-EI/MS/MS, 68 steroids by LC-Ag+CIS/MS/MS, 56 steroids by GC-EI/MS, 54 steroids by LC-ESI/MS/MS, and 27 steroids by GC-ESI/MS/MS were below cut-off value of 2.0 ng/mL. LODs of steroids that formed protonated ions in LC-ESI/MS/MS analysis were all lower than the cut-off value. Several steroids such as unconjugated C3-hydroxyl with C17-hydroxyl structure showed higher sensitivities in GC-EI/MS/MS analysis relative to those obtained using the LC-based methods. The steroids containing 4, 9, 11-triene structures showed relatively poor sensitivities in GC-EI/MS and GC-ESI/MS/MS analysis. The results of this study provide information that may be useful for selecting suitable analytical methods for confirmatory analysis of steroids. Copyright (c) 2015 John Wiley & Sons, Ltd.